Análisis del uso de Tarjetas de Crédito como medio de Pago en la Ciudad de Loja - Quezada Marín, Gabriela Anabel (2017)
The development of this research work has as main objective to analyze the use of credit cards as payment in the city of Loja, study conducted in June 2016; by meeting specific objectives such as: the description of features, functions, elements and the process used by credit cards in the city of Loja, the execution of an exploratory study cardholders Loja, to meet their needs, expectations and how they use their credit cards. Finally it was investigated and established levels of acceptance of the credit card as well as the advantages and disadvantages of its use in commercial premises. In addition it was determined that the research is exploratory-descriptive, being two objects of study, cardholders and commercial premises of Loja; for which the selection technique sample used by the method of non-probability sampling, where the researcher selects the number of objects to be studied, therefore this investigation will be held for 100 cardholders in Loja and 81 local shopping Mall located in Don Daniel, MultiPlaza "La Pradera" and Plaza del Valle shopping, being a real model of transactions with credit cards. bibliographic information is also collected and research techniques were used as observation, survey and statistical graphs to describe the information found. Thus, bibliographic information rose with that were able to confirm that the credit card is a document issued by a financial institution or financial services authorized by the 5 Superintendency of Banks and Insurance of Ecuador, is plastic and currently existing credit cards magnetic and chip band, they have the user's name, the logo of the issuer, card number, expiration date, hologram and other security features; within the functions we find that the credit card is a legal instrument that allows the holder to perform certain operations by replacing the need for cash or other forms of payment. The process used to join credit card issuers is similar for both users and commercial premises. It was also determined, the tangible need for user training before using the credit card, because research found that 96% of users received no preparation before receiving your credit card, with a significant percentage and which, according to the Superintendency of Banks and Insurance of Ecuador (2015) the average monthly consumption with plastic money is $ 300- $ 400 which equals a value above the current basic unified wage in Ecuador. Regarding expectations cardholders, among the most representative values, it was found that 32% of users want to modify the high costs and interest is maintained when using the credit card as payment, 31% expect the current collection logistics improve, while 27% have the expectation that there are other ways to cancel quotas not only through a demand deposit in financial institutions.